PENGARUH PELATIHAN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT. METEC SEMARANG - Bagus Dwi Haryo; Handoyo Djoko Waloejo (Universitas Diponegoro, 2018)
PT. Metec Semarang is one of the foreign owned companies in Tanjung Emas Semarang bonded area, which is engaged in the manufacture of equipment and equipment Vending Machines (Automatic Sales Machine). The purpose of this study is to determine the effect of job training, work motivation and work environment to work productivity of employees of production PT. Metec Semarang. This type of research uses quantitative methods with research type eksplanatory research, with data collection techniques through questionnaires. Population contained in this research that is employees of production of PT. Metec Semarang with the number of samples taken is 100 respondents with Slovin method. Sampling using purposive sampling technique. Analytical methods used are validity test, reliability test, classical assumption test, correlation test, determination test, simple linear regression, multiple linear regression, T test, and F test. In this research assisted by computer program to process data that is SPSS. Based on the results of the study note that job training, work motivation and work environment have a significant effect on employee work productivity, either partially or simultaneously. The independent variable that has the greatest influence on the use decision is the work environment variable. As for suggestions that can be given that remains consistent and provide a variety of job training so that employees are more enthusiastic to follow pelaithan work given the company, provide more intense motivation both morally or materially, maintain and improve the security, comfort and cleanliness of the work environment at PT . Metec Semarang.